Thermal transfer performance of a spherical encapsulated PEG 6000-based composite for thermal energy storage. (15th December 2017) - Anghel, E.M.; Pavel, P.M.; Constantinescu, M.; Petrescu, S.; Atkinson, I.; Buixaderas, E.
Graphical abstract: Highlights: PEG 6000-epoxy composite is a solid–liquid PCM candidate for TES in buildings. PCM solidification is experimentally and modeling evaluated in a spherical module. The approach proposed to solidify the semicrystalline PEG is a two-solid front model. Analytical results agree reasonable with experimental data for PEG solidification. Guidance for PCM solidification in multi-spherical TES systems is provided. Abstract: A polymeric phase change composite material (70 wt% polyethylene glycol, PEG, 6000)-epoxy resin (29 wt%) with aluminum nanopowder (1 wt%) as filler, P60-E, was developed and thermally tested first in a spherical macro capsule in order to be used in thermal energy storage (TES) systems in constructions with low energy consumption. Since the thermal behavior of the phase change component, PEG 6000, is highly influenced by its crystallization behavior, structural and thermal data were correlated. Consequently a high crystallinity degree of 82.6%, found by X-ray diffraction (XRD), for the PEG 6000 component is analogous with values obtained from integrated Raman spectra and DSC data (latent heat of −113.6 J/g) collected at a cooling rate of 0.4 °C/min. Both experimental and mathematical modeling of PEG 6000 solidification in the P60-E nanocomposite was conducted using a single spherical test cell. The heat transfer during solidification assumes time evolution of both liquid and the two solid radial fronts corresponding to crystalline chains of PEG and amorphous counterpart of PEG and epoxy resin in the P60-E composite. Good agreement between experimental values and calculated theoretical curves was found by using a two-front solids model.